SPECIFIC FEATURES OF STRUCTURES IN THE INNER COMA OF COMET C/2017 T2 (PANSTARRS) AS OBSERVED WITH THE OMT-800 TELESCOPE OF THE ODESSA OBSERVATORY TELESCOPE NETWORK - Kleshchenok, V. V.; Kashuba, S. G.; Andrievsky, S. M.; Gorbanev, Yu. M. (Одеські астрономічні публікації, 2020)
Observations of the comet were carried out using the OMT-800 telescope (the primary mirror diameter D = 80 cm; the focal length F = 214 cm) of the Odessa Observatory telescope network from January to June 2020. Image processing was per- formed through standard methods using subtraction of dark and flat field frames. The resulting frames were employed to analyse the morphology of the cometary inner coma using digital filters. Isophotes of the coma and images of its structures appearing as fans and jets were obtained. The presence of a strong fan, which distorts the coma’s standard appearance and makes it elongated perpendicularly to the Sun-comet line, is observed over the period from January to April. Later on, a weak jet that hardly affects the coma’s standard shape appears to replace the fan. The jet reaches its peak intensity near perihelion and then gets fainter rapidly. Such behaviour of the coma structures is indicative of the presence of two active areas on the cometary nucleus surface, for which the matter outflow is governed by the Sun illumination conditions. One of these areas, being more active, is responsible for the appearance of a strong fan. The other area, which is far less active, generates a jet that manifests itself near perihelion. The peak dust production of the comet 120–150 days before perihelion is due to the presence of an active fan in the inner coma.